Analysis of technical and economics overhead transmission line 150 kV construction from mine mouth coal fired power plant to external customer substation - Hadi, Elpatra; Setiabudy, Rudy (Universitas Negeri Padang, 2023)
Mine Mouth Steam Coal Fired Power Plant (PLTU) has a capacity of 2x18MW while the power supplied to internal consumers is 3.6MW or around 10% of the total generating capacity (20% of one generating unit). To operate according to its specifications, the load is increased by operating the load bank. The small internal load and use of the loadbank cause the cost of generation to be high. Excess generating capacity can be sold to external consumers outside the mining area, so it is necessary to build one circuit overhead transmission line 150kV as long 48.38km. The construction of overhead transmission line 150kV from the PLTU to the external consumer substation can increase sales of electricity and can replace the loadbank function. This study aims to evaluate the technical feasibility and economic aspects of the construction overhead transmission line 150kV from the PLTU to an external consumer substation. The research method uses financial indicators IRR, NPV and ROI. Overall, the construction of one circuit overhead transmission line 150kV can increase sales of electricity and replace the function of load bank. The NPV value is IDR 1,604,887,094 with an IRR of 12.53%, and ROI of 9.03 years.